Nilai-Nilai Pendidikan Dalam Tradisi Metatah Memasuki Masa Remaja Dalam Masyarakat Bali Di Desa Minti Makmur Kecamatan Rio Pakava - Ni Luh Sri Puspitasari (PIJAR: Jurnal Pendidikan dan Pengajaran, 2022)
The tooth-cutting ceremony, which is better known as metatah, implicitly has educational values that are still not fully understood by the community, although so far this ceremony has been interpreted by some as debt repayment, without understanding the other values contained therein. The purpose of the metatah ceremony is to clean someone's teeth chatter, anger, greed (Sad Ripu) and as a symbol will cut 6 upper teeth namely 4 incisors and 2 canines. This research method uses qualitative research with a phenomenological approach. The tooth-cutting or metatah ceremony can be carried out if the child has reached adulthood, that is, women are marked with menstruation and men's voices are enlarged. The procedure and sequence of the metatah tradition in Balinese society in Minti Makmur Village, Rio Pakava District (1) the procedure and sequence of the metatah procession, namely sungkem, then to the carving center, teeth sharpened, smoothing whetstones, treating the sharpened teeth, then picking and pawintean; (2) the meaning of metatah procession for parents is as a duty and obligation towards children. The meaning of the metatah procession for children is the gateway to adolescence and therefore how can it reflect good adolescent behavior in accordance with the purpose of the metatah procession.